The effectiveness of moxifloxacin in the treatment of community-acquired pneumonia (Perioperaciina Medicina, 2021)
The article presents the results of domestic and international studies of the use of the fourth-generation fluoroquinolone moxifloxacin in the treatment of commu-nity-acquired pneumonia and pneumonia caused by SARS-CoV-2. Analysis of the clinical use of moxifloxacin in the treatment of complications of the respiratory tract infec-tions indicates its high efficiency and bioavailability, a low risk of resistance, which makes it possible to recommend it for widespread use in the work of a practicing doctor. Ge-neric drug Maxicin (Yuria-Pharm), available as a 20 mg/ml concentrate in a 20 ml vial, can significantly reduce the cost of treatment and optimize infusion therapy by choosing both volume and solvent.
Keywords: fluoroquinolones; moxifloxacin; treatment; pneumonia; COVID-19